2013
DOI: 10.18517/ijaseit.3.1.268
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Colour and Strength Changes of Eco-friendly Hot Oil Treatment on 15 Year-old Cultivated Acacia Hybrid

Abstract: The chemical, colour and strength properties of thermally modified cultivated 15-year-old Acacia hybrid were investigated. Logs of A. hybrid were harvested and cut at the bottom, middle and top sections. The wood later underwent hot oil thermal modification using palm oil at temperatures 180°C, 200°C and 220°C for 30, 60 and 90 min. Untreated wood was used as control. The hot oil thermal modification process caused some features changed in the chemical composition, colour appearances and strength properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
2
1
0
2
Order By: Relevance
“…These results have also been reported by Wahab et al (2011). Kamdem et al (2002) have suggested that the increase in lignin conten is probably due to the reduction of other wood components and does not imply that new lignin is formed.…”
Section: Fig 5 Relative Lignin Content Compared To Ctrl In Sapwood supporting
confidence: 86%
See 1 more Smart Citation
“…These results have also been reported by Wahab et al (2011). Kamdem et al (2002) have suggested that the increase in lignin conten is probably due to the reduction of other wood components and does not imply that new lignin is formed.…”
Section: Fig 5 Relative Lignin Content Compared To Ctrl In Sapwood supporting
confidence: 86%
“…4), the lignin contents were always greater in heartwood, with the only exceptions coming from samples treated only with heat (Ctrl+H120 and Ctrl+H180). Similar results were found by Wahab et al (2011) in Acacia hybrid wood treated with hot oil, where the lignin content of heartwood was greater than that in sapwood. The differences in chemical composition in the wood, in terms of extractives, cellulose, and hemicellulose (Cao et al 2012) content, could be due to the lignin concentration in sapwood and heartwood.…”
Section: Ligninsupporting
confidence: 86%
“…Next, the teak wood was put into a metal cage and then submerged into the heated oil. The whole process was monitored by a control panel outside the machine [24,25,26]. Once treated, the wood is then removed from the tank, and the residual oil is wiped clean with a cloth to prevent oil absorbance into the wood.…”
Section: Methodsmentioning
confidence: 99%
“…Penurunan kadar holoselulosa tersebut lebih besar dibandingkan di Pinus calibria yang dipanaskan pada suhu 130-230°C dalam waktu 2 dan 8 jam maupun kayu Mongolian pada suhu 240°C (Ding et al, 2011). Kisaran nilai penurunan kadar selulosa dan hemiselulosa sesuai pada kayu Acacia hybrid dengan perlakuan suhu 220°C selama 90 menit (Wahab et al, 2011).…”
Section: A Komponen Dinding Sel Kayuunclassified